Emphysematous Gastritis and Portal Venous Gas - Mohamed Abugrin; Kai Mebust (Annals of Internal Medicine: Clinical Cases)
We present a rare case of emphysematous gastritis and portal venous gas triggered by severe sepsis, likely causing gastrointestinal hypoperfusion, transmural ischemia, and ileus. This condition facilitated the local translocation or hematogenous spread of gas-forming organisms into the gastric wall. Prompt identification of computed tomography findings and early initiation of therapy led to favorable outcomes. This case highlights a critical medical scenario that requires swift diagnosis and intervention.